Cost of equity calculation for non-traded companies - CAPM and AHP comparison analysis - Strosin, Przemyslaw (My University, 2011)
The main purpose of this paper is to introduce the reader to the general topic of capital costs, especially the cost of equity capital and its estimation. Due to the shortage of this paper many different or “classic” approaches will be brought up and explained, but only CAPM will be applied and put in contrast to one alternative approach. This alternative sophisticated tool is called the Alternative Hierarchy Process. It has a uniqueness, which allows the user to incorporate every important aspect of the company’s business as well as other unique qualities. The author states that AHP, because of its possibilities, is better suited for the estimation of the cost of equity capital and therefore delivers more reliable results than CAPM does. A company operating in the Austrian medical sector will be evaluated for this purpose and the results, of both approaches, will be compared with each other. Finally it has to pointed out that CAPM is never the less a good approach, but only for rated companies, since it accuracy is dependent on the data available. Therefore it could only supposedly be applied in not trade companies with a very long history, since it was proven that low data frequencies and economic disturbances sophisticate the results. Not trade companies and especially very small properly functioning companies present such unique qualities that an estimation of equity returns can turn out to be a surprise in every direction, but more than less predictable with a methodology that incorporate this uniqueness.
Kalkulacja kosztu kapitału własnego dla firm nie notowanych na giełdzie papierów wartościowych- CAPM i AHP analiza porównawcza
Keywords: cost of equity; comparison analysis; companies; calculation